Effect of yoga boat pose on weight loss in 3-month injectable contraceptive receptors - Lutfi Fitriana; Luluk Yuliati; Irfana Tri Wijayanti (Institute of Computer Science (IOCS), 2023)
Weight gain in injectable contraceptive acceptors is one of the most common side effects. Long-term weight gain can lead to obesity. One of the complementary therapies that can be done by injectable contraceptive acceptors to lose weight is to do yoga boat pose. Of the 674 acceptors who used 3-month injectable contraceptives at Hadimulyo Health Center there were 75 people who experienced excessive weight gain. The yoga boat pose was given to 75 acceptors. Body mass index measurements were taken before and after the implementation of yoga. The instruments used were a weight measuring device, a height measuring device and an observation sheet for the implementation of yoga boat pose. Data analysis was carried out with the Wilcoxon Test. The results of BMI measurements before treatment showed that most samples had BMI in the obese category (74.67%) with an average BMI of 24.80 and an average body weight of 60.05 kg, while after treatment showed a decrease in the number of obese categories to (73.33%) with an average BMI of 24.55 and an average body weight of 59.41 kg. There is an effect of Yoga Boat Pose on the weight of 3-Month Injectable Contraceptive Receptors in the Hadimulyo Health Center Work Area, Mesuji Regency Lampung (p = 0.001). Yoga Boat Pose can be applied as a complementary therapy for weight loss in 3-month injectable contraceptive acceptors who experience excessive weight gain.